1999
DOI: 10.1016/s0893-133x(99)00030-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Psychopathology to the Human Serotonin1B Genotype and Receptor Binding Kinetics in Postmortem Brain Tissue

Abstract: Knockout of the 5-HT 1B gene in mice results in increased aggression, as well as alcohol and cocaine consumption. Given the clinical association of aggression, suicide, alcoholism, and substance abuse, we studied relationship of psychopathology to the human 5-HT 1B receptor gene (N ϭ 178) and postmortem human 5-HT 1B receptor binding (N ϭ96Several neuropsychiatric disorders such as mood disorders, substance abuse, or alcoholism have been associated with dysfunctions of the central serotonergic system (Coppen 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
102
3
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 44 publications
22
102
3
1
Order By: Relevance
“…A recent study found that the 861G allele was associated with 20% fewer receptor binding sites than 861C. 24 A defective receptor or decreased expression of these receptors could result in a dysfunction in serotonin neurotransmission, which is consistent with the hypothesis that abnormal 5-HT levels influence behaviour, particularly impulsivity.…”
supporting
confidence: 58%
“…A recent study found that the 861G allele was associated with 20% fewer receptor binding sites than 861C. 24 A defective receptor or decreased expression of these receptors could result in a dysfunction in serotonin neurotransmission, which is consistent with the hypothesis that abnormal 5-HT levels influence behaviour, particularly impulsivity.…”
supporting
confidence: 58%
“…A recent post-mortem study has suggested differences in the number and in the pharmacological properties of the 5HT1D␤ sites between subjects heterozygous and homozygous for the G variant (Huang et al 1999). However, further investigations are needed to better clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…G861C, or most likely a variant in linkage disequilibrium with G861C, exhibits functional effects. Investigating variants of the 5-HT1B receptor in major depression, most of the studies do not find an association between the 5-HT1B receptor and major depression (Huang et al 1999;Fehr et al 2000;Tsai et al 2004). A single postmortem study investigating prefrontal cortical 5-HT1B receptor binding did not find differences between major depression and controls (Huang et al 1999).…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…Investigating variants of the 5-HT1B receptor in major depression, most of the studies do not find an association between the 5-HT1B receptor and major depression (Huang et al 1999;Fehr et al 2000;Tsai et al 2004). A single postmortem study investigating prefrontal cortical 5-HT1B receptor binding did not find differences between major depression and controls (Huang et al 1999). A cofactor of the 5-HT1B receptor, S100A10 (also termed p11) has been suggested to play a role in depression (Svenningsson et al 2006); however, its effect may also relate to anxiety.…”
Section: -Ht Receptorsmentioning
confidence: 99%